Involvement of PPARγ in the Anticonvulsant Activity of EP-80317, a Ghrelin Receptor Antagonist - Lucchi, Chiara; Costa, Anna M.; Giordano, Carmela; Curia, Giulia; Piat, Marika; Leo, Giuseppina; Vinet, Jonathan; Brunel, Luc; Fehrentz, Jean-Alain; Martinez, Jean; Torsello, Antonio; Biagini, Giuseppe (Frontiers in Pharmacology, 2017)
Ghrelin, des-acyl ghrelin and other related peptides possess anticonvulsant activities. Although ghrelin and cognate peptides were shown to physiologically regulate only the ghrelin receptor, some of them were pharmacologically proved to activate the peroxisome proliferator-activated receptor gamma (PPARγ) through stimulation of the scavenger receptor CD36 in macrophages. In our study, we challenged the hypothesis that PPARγ could be involved in the anticonvulsant effects of EP-80317, a ghrelin receptor antagonist. For this purpose, we used the PPARγ antagonist GW9662 to evaluate the modulation of EP-80317 anticonvulsant properties in two different models. Firstly, the anticonvulsant effects of EP-80317 were studied in rats treated with pilocarpine to induce status epilepticus (SE). Secondly, the anticonvulsant activity of EP-80317 was ascertained in the repeated 6-Hz corneal stimulation model in mice. Behavioral and video electrocorticographic (ECoG) analyses were performed in both models. We also characterized levels of immunoreactivity for PPARγ in the hippocampus of 6-Hz corneally stimulated mice. EP-80317 predictably antagonized seizures in both models. Pre-treatment with GW9662 counteracted almost all EP-80317 effects both in mice and rats. Only the effects of EP-80317 on power spectra of ECoGs recorded during repeated 6-Hz corneal stimulation were practically unaffected by GW9662 administration. Moreover, GW9662 alone produced a decrease in the latency of tonic-clonic seizures and accelerated the onset of SE in rats. Finally, in the hippocampus of mice treated with EP-80317 we found increased levels of PPARγ immunoreactivity. Overall, these results support the hypothesis that PPARγ is able to modulate seizures and mediates the anticonvulsant effects of EP-80317.